2015
DOI: 10.1016/j.jpainsymman.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Psychosocial Outcomes Among Bereaved Siblings of Children With Cancer

Abstract: Context The death of a child from cancer affects the entire family. Little is known about the long-term psychosocial outcomes of bereaved siblings. Objectives To describe: (1) the prevalence of risky health-behaviors, psychological distress, and social support among bereaved siblings; (2) potentially modifiable factors associated with poor outcomes. Methods Bereaved siblings were eligible for this dual-center, cross-sectional, survey-based study if they were ≥16 years-old and their parents had enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 34 publications
9
107
0
5
Order By: Relevance
“…For example, in a dual-centre survey 68 of 58 bereaved siblings of children with cancer, respondents reported that their anxiety, depression, and substance use increased in the first year following the death of their sibling. Those who felt dissatisfied with the end-of-life communication, who were poorly prepared for the death of their sibling, or who had not had a chance to say goodbye reported higher ongoing distress and lower current social support.…”
Section: Current Era Of Ppc Oncology Research (2010 To Present)mentioning
confidence: 99%
“…For example, in a dual-centre survey 68 of 58 bereaved siblings of children with cancer, respondents reported that their anxiety, depression, and substance use increased in the first year following the death of their sibling. Those who felt dissatisfied with the end-of-life communication, who were poorly prepared for the death of their sibling, or who had not had a chance to say goodbye reported higher ongoing distress and lower current social support.…”
Section: Current Era Of Ppc Oncology Research (2010 To Present)mentioning
confidence: 99%
“…A menudo, los cuidados del equipo de salud se concentran en los padres del niño y se deja de lado a los hermanos, quienes también viven una experiencia traumática no solo por la muerte del niño, sino por el abandono no intencionado de sus padres (54,55). Esta revisión puso de relieve lo importantes que son las personas en la vida de los padres que pierden a su hijo a causa del cáncer infantil; en particular, se reportó la importancia de recuperar las relaciones con los otros hijos y cómo, a través de ello, el sentirse necesitado, aporta motivos para continuar viviendo.…”
Section: El Haber Participado Enunclassified
“…22 Many studies have recruited samples from support groups or advertisements introducing sample bias with data collection up to 20 years after the sibling’s death. 4,23,24 Studies include deaths of newborns to 30-year-old adult children in the same sample. 25 There is very little research on adolescents’ reports of their reactions to sibling death in the NICU/PICU.…”
Section: Adolescents’ Responsesmentioning
confidence: 99%